COORDINATED HIGH-LATITUDE EXPERIMENTS FOR THE SIMULATION OF NUCLEAR-BURST EFFECTS ON VLF SYSTEMS. - Griffin, G. A.; Haas, R. W.; Imhof, G. W.; Lambert, N. E.; Musser, J. M. (1967)
This report describes some coordinated high-latitude experiments for simulating nuclear-burst effects on long-range VLF propagation. The program consists of six parts: (1) Collection and study of VLF phase and amplitude data over six long-range, high-latitude VLF propagation paths and 2 middle latitude control paths; (2) Collection and study of ionospheric data (cosmic noise absorption data) near Reykjavik, Iceland, and Thule, Greenland; (3) Collection and study of other VLF data and ionospheric data from external sources (including satellite data); (4) Study and comparison of items 1 through 3 with nuclear test VLF data; (5) Collection and study of rapid phase VLF data at Thule, Greenland; and (6) Installation and operation of a patrol spectrograph to study polar glow auroral effects.